Accounting Factors and Quality of Life Influencing the Saving Behavior of Working-Age Individuals in Nonthaburi Province - จำลองพันธ์, วนิดา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
Accounting Factors and Quality of Life Influencing the Saving Behavior of Working-Age Individuals in Nonthaburi Province aimed to examine the impact of accounting-related factors and quality of life on their saving behavior. Four hundred working-age individuals residing in Nonthaburi Province were selected as the sample group for this study. Period: January - March 2025, A structured questionnaire was designed using Taro Yamane’s formula, and participants were selected through a convenience sampling method. The study's findings revealed that several factors contributing to a good quality of life, such as a safe and health-supportive work environment, appropriate social integration and a balance between work and personal life, had a statistically significant influence on saving behavior at the 0.05 level.